Evaluating The Implementation of The Village Fund Policy in Tilongkabila District, Bone Bolango Regency: A Qualitative Study of Planning, Execution, And Supervision. - Hadjaratie, Srininang; Abdussamad, Zuchri; Tui, Fenti Prihatini; Badjuka, Alexander H. (Abdurrauf Science and Society, 2025)
This study examines the implementation of the Village Fund Policy (Dana Desa) in Tilongkabila District, Bone Bolango Regency, within Indonesia’s decentralization framework. Although the Village Fund aims to promote participatory and equitable rural development, its implementation has often been constrained by administrative and structural barriers. The research employs a qualitative descriptive design using a case study approach across three villages Permata, Bongopini, and Iloheluma. Data were collected through in-depth interviews, observation, and document analysis involving 10–15 key informants, including village heads, members of the Village Consultative Body (BPD), and community representatives. Data were analyzed using Miles and Huberman’s (1994) interactive model consisting of data reduction, display, and conclusion drawing, and validated through triangulation and member checking. The findings reveal that planning processes are formally participatory but dominated by village elites, implementation tends to prioritize physical projects over empowerment programs, and supervision remains weak due to limited technical capacity and irregular district monitoring. Using Edward III’s implementation model, four key factors were identified: (1) communication, unclear dissemination of central directives; (2) resources, inadequate training and technical expertise; (3) disposition, uneven commitment among implementers; and (4) bureaucratic structure, rigid and overlapping reporting mechanisms. These findings demonstrate that the success of policy implementation depends not only on institutional frameworks but also on behavioral and contextual dimensions. The study contributes theoretically by validating Edward III’s model in a village governance context and practically by recommending strategies for administrative simplification, participatory planning, capacity-building, and community-based supervision. It concludes that effective decentralization requires not only fiscal transfer but also the transformation of local administrative behavior, communication, and institutional learning.